Characteristics of Pregnant Women who Experienced Chronic Energy in the Working Area of Puskesmas Rancabali, Bandung District - Yanyan Mulyani; Siti Neneng Sri (Journal of Global Research in Public Health, 2020)
Energy is the most important nutritional factor during pregnancy that can affect the birth weight of the baby. Pregnant women who experience the risk of chronic energy deficiency (KEK) will cause several problems, both for the mother and the fetus. The purpose of this study was to determine the characteristics of pregnant women who experience chronic energy deficiency in the working area of ​​the Rancabali Health Center, Bandung Regency. Research design using descriptive. The population was 274 people, the sample was 73 people and the sample was taken by simple random sampling. Primary data collection is interviews using a checklist sheet with data analysis using univariate analysis. The results showed that more than half occurred at the age <20 years as many as 41 people (56.2%), more than half of them with low education as many as 53 people (72.6%), more than half with primigravida parity of 52 people (71, 2%) and more than half with low income as many as 53 people (72.6%). The conclusion is that more than half of the incidence of KEK occurs at age <20 years, low education, primigravida parity and low income. Suggestions for the health center for health education regarding nutrition, especially for pregnant women and also to increase the socialization of the Supplementary Feeding program.